Schizophrenia genes, gene expression, and neuropathology: on the matter of their convergence. - Harrison, P; Weinberger, DR (2005)
This review critically summarizes the neuropathology and genetics of schizophrenia, the relationship between them, and speculates on their functional convergence. The morphological correlates of schizophrenia are subtle, and range from a slight reduction in brain size to localized alterations in the morphology and molecular composition of specific neuronal, synaptic, and glial populations in the hippocampus, dorsolateral prefrontal cortex, and dorsal thalamus. These findings have fostered the view of schizophrenia as a disorder of connectivity and of the synapse. Although attractive, such concepts are vague, and differentiating primary events from epiphenomena has been difficult. A way forward is provided by the recent identification of several putative susceptibility genes (including neuregulin, dysbindin, COMT, DISC1, RGS4, GRM3, and G72). We discuss the evidence for these and other genes, along with what is known of their expression profiles and biological roles in brain and how these may be altered in schizophrenia. The evidence for several of the genes is now strong. However, for none, with the likely exception of COMT, has a causative allele or the mechanism by which it predisposes to schizophrenia been identified. Nevertheless, we speculate that the genes may all converge functionally upon schizophrenia risk via an influence upon synaptic plasticity and the development and stabilization of cortical microcircuitry. NMDA receptor-mediated glutamate transmission may be especially implicated, though there are also direct and indirect links to dopamine and GABA signalling. Hence, there is a correspondence between the putative roles of the genes at the molecular and synaptic levels and the existing understanding of the disorder at the neural systems level. Characterization of a core molecular pathway and a 'genetic cytoarchitecture' would be a profound advance in understanding schizophrenia, and may have equally significant therapeutic implications.